Factors Influencing the Physician’s Commitment to Visualization - حسن حيدر فليح; مشتت علياء زامل (Journal of Legal Sciences, 2019)
The doctor’s commitment to medical visualization is influenced by several factors for the different patients in terms of the nature of the disease, the seriousness of the disease, the age of the patient and the aim of being subject to medical interference, as there are circumstances surrounding the patients oblige the doctor to reduce the eviction towards them, by hiding medical information, The physician must make a firm commitment by extending the scope of his vision to a wider range than in ordinary medical work Therefore, we will discuss in this regard cases where the lightening of medical clarification and cases that require emphasis in the following order: